(untitled) (The Batuk, 2019)
Teacher identity remains as a major issue of research in the field of teachers’ professional development. Understanding the construction of teacher identity is important to fully understand how teachers negotiate their selves with broader institutional power relations and to discuss how teachers invest their agency in building their professional identity. This phenomenological study analyzes the experiencesof six university lecturers with a focus on teacher identity construction in relation to broader institutional culture. This show study shows that university lecturers, who are at the bottom of professional hierarchy, do not receive much institutional support nor are they mentored by their seniors. More strikingly, the study reveals academic identity of the university lecturers are not recognized due to growing culture of partisan politics. This culture has also created sense of fear and unfriendly collegial relations.